ANALISIS PERBANDINGAN KINERJA KEUANGAN PT ASTRA AGRO LESTARI TBK PADA TAHUN 2022-2023 - Nadiya Ayunita; Dody Shinto Prabowo; Ari Andri Wibowo; Sri Hermuningsih (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the financial performance of PT Astra Agro Lestari Tbk using ratio analysis, which includes liquidity, activity, debt, and profitability ratios. The data used are taken from the company's financial statements for 2022 and 2023. The results of the analysis show that the liquidity ratio of PT Astra Agro Lestari Tbk is below the industry standard, indicating liquidity risk. There are fluctuations in the ratio, reflecting challenges in asset management. On the other hand, the company's debt ratio (DER) shows stability, but requires more attention in long-term debt management. In addition, the profitability ratio also shows fluctuations, with several years showing less than optimal performance. Overall, this analysis indicates challenges in the financial performance of PT Astra Agro Lestari Tbk that need to be addressed in order to achieve sustainable growth. This study is expected to provide useful insights for management and stakeholders in strategic decision making. Keywords: Activity Ratio; Debt Ratio; Financial performance; Liquidity Ratio; Profitability Ratio.